1994
DOI: 10.1007/bf03347690
|View full text |Cite
|
Sign up to set email alerts
|

The duration of prolactin secretory bursts from the pituitary is independent from both prolactin and gonadal steroid plasma levels in women and in men

Abstract: The intrinsic secretory characteristics of prolactin (PRL) have been investigated using newly developed algorhythms for instantaneous secretory rate (ISR) computation. PRL secretory rate, its intrinsic pulsatile characteristics and their possible dependance from gonadal steroids were investigated in five groups of subjects: a) 11 women during the follicular and luteal phase of the same menstrual cycle; b) 5 healthy postmenopausal women; c) 6 women affected by functional hyperprolactinemia; d) 5 normal men; e) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

1997
1997
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…However the role of estrogens in regulating PRL secretion is certainly not straightforward. During the menstrual cycle no influence of different estradiol concentrations on PRL is demonstrable, but in this study only part of the 24 h cycle was analyzed [32]. Furthermore, the PRL increase after TRH injection is independent of the stage of the menstrual cycle [33].…”
Section: Discussionmentioning
confidence: 95%
“…However the role of estrogens in regulating PRL secretion is certainly not straightforward. During the menstrual cycle no influence of different estradiol concentrations on PRL is demonstrable, but in this study only part of the 24 h cycle was analyzed [32]. Furthermore, the PRL increase after TRH injection is independent of the stage of the menstrual cycle [33].…”
Section: Discussionmentioning
confidence: 95%
“…In our study, mean serum prolactin levels were significantly increased during interferon therapy. As it has been demonstrated that the duration and frequency of prolactin secretory bursts from the pituitary are independent from gonadal steroid plasma levels in women and in men (Genazzani et al 1994), we assume that the observed increase in mean serum prolactin values is not secondary to alterations in gonadal steroid concentrations. Rather we may speculate that interferon therapy either directly affected lactotrope cells in the pituitary, or hypothalamic factors which control prolactin secretion, or both.…”
Section: Discussionmentioning
confidence: 73%
“…But Genazzani and associates have shown that the duration of prolactin burst from the pituitary is independent from both prolactin and gonadal steroidal hormones. 53 As the LH and FSH response to exogenous GnRH is frequently normal or frankly excessive in these patients suggesting a normal pituitary gonadotrophin reserve, the defect is likely to reside in the hypothalamus and is generally thought to be a functional and potentially reversible alteration in GnRH secretion. 54 Severe hyperprolactinemia (prolactin b 2000 mUal) may cause hypogonadism and is almost invariably associated with sexual dysfunction in the male.…”
Section: Hyperprolactinemia and Hypogonadism In Manmentioning
confidence: 99%